Integration of Active And Passive Cool Roof System For Attic Temperature Reduction In Guardhouse - Lingeswaran, Sundaramoorthy (2020)
This research project investigates the cooling effect of a roof system which is designed to enhance the comfort ability of guardhouse occupants with attic temperature reduction. Malaysia is considered as an equatorial climate country which having a hot-humid climate all the year. Therefore, an ideal cool roof system was developed with the implementation of thermal reflection coating (TRC), vacuumed rockwool insulation, polished aluminium sheet and solar powered fan for ventilation system as a space cooling device for houses in Malaysia. The selection of an efficiency cool roof system is carried out with a total of eight models fabricated and experimented for each aspect of heat transfer mechanisms (conduction, convection and radiation). The design that shows the best cooling efficiency is selected and implemented into the main design which is design X. The model simulation was carried out in a heating chamber by utilising the halogen lamp as the replacement for solar irradiation provided by the sun. Two passive cooling method were introduced in this research project which are vacuumed rockwool insulation and polished aluminium sheet. For vacuumed insulation, it was able to reduce 1.75 °C compared to normal insulation. For polished aluminium, sheet it was able to reduce 1.5 °C compared to unpolished aluminium sheet. Besides that, one active cooling method was introduced which is solar powered fan. The solar powered fan is consider as forced convection. Where it was compared to a ventilation hole which is consider natural convection. Hence from the results forced convection was able to reduce 1.25 °C more than natural convection. The result of this eco-friendly cool roof system (design X) has successfully reduced the attic temperature by 8.5 °C compared to the normal roof model (design A). As a result, this integrated cool roof design comprises the ability to enhance the comfort of guardhouse occupants with sustainable renewable energy.